DEVELOPMENT OF TEACHING MATERIAL WITH BRIDGING ANALOGY: LESSON PLAN & MODULE - Febiana Gita; Finola Marta Putri; Gelar Dwirahayu (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2022)
This study aims to develop teaching materials consisting of a lesson plan and module with the Bridging Analogy Approach for subject matter Relations and Functions. Bridging Analogy is an approach that connects new concepts with analogous real-life problems for the student to a new concept in math by looking for the similarity between the analogy and the new concept. The research method used is Research and Development (R&D), consisting of Define, Design, and Develop and for the disseminate can't be implemented because of pandemic covid-19. The expert and student judged the teaching material. The expert who asses the teaching material consists of 3 lectures from the Math Department and two Junior High School practitioners. The score for the teaching material with Bridging Analogy by the expert is 93.83%, which means the lesson plan is